Study guide : HBEC 4203 Assessment in early childhood education - Badzis, Mastura; Abdullah, Nor Faizah (Open University Malaysai (OUM), 2013)
this course is designed to expose educators to various types of assessment in early childhood education. it will discuss types of observatipon and recordimng tools, as well as the advantages and disadvantages associated with each. you will learn how to set goals, plan, and choose the best instrument for specific situations, and gain techniques of organising, analysing and interpreting observation data. in addition, this course will teach you how to apply assessment information to improve programme quality and to best meet needs of individual children. you will also study the proper methods of communicating observation and assessment information to parents